Autonomia privada e licença para mentir: uma investigação sobre a possibilidade de limitação contratual da responsabilidade por dolo - Sabadin, Mariana Guerra (2015)
This master’s dissertation aims at investigating whether the parties to business deals executed in accordance with Brazilian law can evoke the party autonomy to – through the inclusion in the contract of mechanisms imported from the common law – such as representations and warranties, rules regarding indemnification and limitation of liability (generally accompanied by exclusive remedy clauses), entire agreement clauses and disclaimer os reliance clauses –, limit their extracontractual liability for fraud (dolo) set forth in the Brazilian Civil Code and, therefore, create a true license to lie. In view of the lack of judicial precedents on this issue in Brazil, this dissertation analyzes the case 'Abry Partners V, L.P. v. F&W Acquisition LLC, C.A. No. 1756-N' examined by the Court of Chancery of the State of Delaware in 2006 in order to (i) comprehend – according to the decision of such Court of Chancery and to the foreign literature that has studied the case – the intended and actual effects of such clauses and mechanisms within the common law system; and, afterwards, (ii) attempt to understand – according to the principles applicable to the formation, conclusion and interpretation of commercial agreements in Brazil (such as the objective good faith) – how the Brazilian Judiciary should conduct the accommodation and/or adaption of such clauses and mechanisms to Brazilian law.